Impact of Management Information Systems on Enterprise Decision Support - Wang, Yueer (International Journal of Global Economics and Management, 2024)
This thesis examines the impact of management information systems (MIS) on decision support in business, focusing on the role of MIS in improving data availability, enhancing data analysis capabilities, improving decision-making efficiency and supporting collaborative decision-making. Through real-world case studies of large manufacturing companies and retail businesses, the paper demonstrates how MIS implementation can significantly improve productivity, inventory management, and customer satisfaction. The manufacturing company in Case 1 improved production line efficiency and inventory management, reduced inventory costs, and enhanced decision support by integrating an MIS platform. The retail enterprise in Case 2 achieved sales growth, inventory optimisation and customer satisfaction through real-time data analytics and CRM systems. The paper concludes that the application of MIS in modern enterprises can effectively improve the quality of decision-making and operational efficiency, and provide important support for enterprises in complex market environments. Through an in-depth analysis of MIS functions and their impact, the paper provides useful references and lessons for enterprises in the implementation and optimisation of decision support systems.